Dos Santos Albasini, João (1876–1922) - Morais, Isabel (The International Encyclopedia of Revolution and Protest, 2009)
Born in Magule, Mozambique (Portuguese East Africa), João dos Santos Albasini was a mulatto, the leading intellectual in the main center, Lourenço Marques (today, Maputo), the editor of O Africano (The African) founded 1908, and O Brado Africano (The African Voice) founded in 1918, and a champion of worker and African rights. Often characterized as a republican and a moderate, Albasini had a basic education and an appetite for ideas. He was an avid reader of republican theory, syndicalism, and anarchism – all influential in Portugal – and was familiar with a range of radical ideas circulating in the city's thriving café culture.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781405198073.wbierp0473
Keywords: 1800-1899; 1900-1999; Africa; Southern Africa; bibliography; colonialism; comparative history; imperialism; political history